NoiseAware: System for Real-Time Noise Monitoring in Smart Cities - Moreira Neto, Maurício; Gomes, Francisco; Silvestre, Vitória (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2023: Anais do L Seminário Integrado de Software e HardwareDO - 10.5753/semish.2023.230580, 2023)
The Internet of Things (IoT) is an emerging paradigm that combines several technologies. IoT provides the interconnection of physical devices for exchanging information among them and provides services to the users. The urban environment is susceptible to various kinds of noise from different sources. Therefore, a system is needed to monitor the urban environment’s noise level. NoiseAware is a noise monitoring system for smart cities. NoiseAware monitors the noise levels of a particular location and sends an alert to the competent bodies to operate on site when the level reaches the allowable threshold. According to the literature review conducted, we did not find any work related to noise monitoring that has systems integration, accords real-time requests, and uses more than one communication protocol. NoiseAware has considerable service availability (approximately 81%) for system users, and the load tests show it has relevant request capability.